Liver integrity and functionality in a population of goat livestock guardian dogs living in the dry forest of southern Ecuador: Liver integrity and functionality in a population of goat livestock guardian dogs living in the dry forest of southern Ecuador (Veterinary Science, 2025)
In the seasonal dry forest ecosystem of southern Ecuador, goat breed is extensively carried out and protected by native dogs known as "Ganachos," whose primary function is to guard the livestock from potential wild predators. Evaluating their liver health is essential to ensure the well-being of these dogs raised under specific conditions. The study included 60 dogs (21 ♀, 39 ♂), considering in this analysis 2 enzymes associated with liver integrity: Alanine aminotransferase (ALT) and Aspartate aminotransferase (AST) and 8 analytes related to liver funtion: Alkaline phosphatase (ALP), Gamma glutamyl transpeptidase (GGT), Albumin, Total proteins (TP), Urea, Cholesterol, Bilirubin and Glucose. Taking as independent variables sex, age (puppies, adults and geriatric), size only in adults and geriatric (small: 51 cm) and habitat location (low: 0-500 masl, medium: 500-1000 masl and high: >1000 masl). All parameters were within the reference ranges except bilirubin, whose value was above the same, enzymes such as GGT, ALP, Urea and Bilirubin showed high variability and when analyzing the variables considered in the study, a significant statistical difference was determined in age (albumin, PT and cholesterol) and in habitat location (ALT and bilirubin). In conclusion, the poor handling and feeding conditions of these animals negatively affect their liver integrity. Factors such as low-protein diets, dehydration, prolonged fasting, liver damage, and cholestasis associated with hemoparasites present in the ecosystem contribute to the deterioration of their health, well-being, and life expectancy
Keywords: Ganacho dog; liver enzymes; Chusca goat